PENINGKATAN KINERJA KARYAWAN MELALUI BUDAYA ORGANISASI DAN DISIPLIN KERJA KARYAWAN PADA PT PLN INDONESIA POWER UBP SURALAYA KOTA CILEGON - Muhammad Faiz; Khaeruman Khaeruman; Edi Muhammad Abduh Al Hamidi (JURNAL EKONOMI BISNIS DAN MANAJEMEN, 2024)
Human resources are the main asset for a company. Resources that have intellect, feelings, desires, abilities, and skills. All potential human resources greatly affect efforts to achieve the goals of an organization. So that between the organization and the individual in it is an unusual talent to be separated. Because the role of human resources is very important for an organization. Discussing cultural issues itself is essential for an organization or company, because it will always be related to the life in the organization. Organizational culture is a philosophy, ideology, values, assumptions, beliefs, hopes, attitudes and norms that are shared and binding in a certain community. Why is organizational culture important, because it is the habits that occur in the organizational hierarchy that represent the norms of behavior that are followed by the members of the organization. A productive culture is one that can make an organization strong and the company's goals can be accommodated.This study aims to find out the Improvement of Employee Performance through Organizational Culture and Employee Work Discipline at PT PLN Indonesia Power UBP Suralaya, Cilegon City.The method used in this study is the method of causal associative and by using a quantitative approach. The data collection technique used is by distributing questionnaires, with a population of 93 employees. The sampling technique uses a saturated sampling technique where all members of the population are sampled.The results of this study show that based on the results of the T test of Organizational Culture that obtained a value of tcount greater than ttable (3.148 > 1.986) with a significance value of less than 0.05 Partially, there is an influence of organizational culture on employee performance. So H0 was rejected and Ha was accepted. Work discipline value tcount greater than ttable (3,480 > 1,986) with a significance value of less than 0.05. So there is a partial Influence of Work Discipline on Employee Performance. So H0 rejected and Ha Accepted. Grade Fcount of 9.775 this result was then compared to Ftable. With a significant level (α) of 0.000, and df: n-k-1 = 93-2-1 = 90, the value f can be obtainedtable by 3.10. Because of the F gradecount 9.775 greater than ftable 3.10, then Ha is accepted.The conclusion in this study is that Organizational Culture and Work Discipline partially and simultaneously have a significant influence on Employee Performance at PT PLN Indonesia Power UBP Suralaya, Cilegon City.